Sustaining the Effective Use of Health Care Data: A Message from the Editors - Wilcox, Adam (EGEMS (Wash DC), 2014)
INTRODUCTION: Over the past decade, several initiatives have funded large projects to develop clinical research data infrastructures totaling several hundred million dollars. While most of this funding has ended or is expected to end soon, the projects themselves must struggle to continue operations beyond the initial funding. Examples of sustained research-data infrastructures are lacking, and recommended approaches to improve sustainability of developing infrastructures are even rarer. Early on, the Electronic Data Methods (EDM) Forum—and the Agency for Healthcare Research and Quality (AHRQ) as its sponsor—recognized the need to study strategies for sustainability. THEMES: Three prominent themes relating to sustainability arise among the articles in this special issue: the importance of project maturity, commercialization activities, and stakeholder support. Maturity was relevant to all the papers since a project’s maturity directly influences the opportunities that are available, while commercialization and stakeholder support emerged from comparisons among subsets of articles. NEXT STEPS: The papers in this issue create a useful initial set of case studies to help in understanding sustainability issues for data infrastructures needed for research and QI. Each paper includes important lessons learned from the authors’ experience with the different projects that should resonate with the broader fields of clinical research and clinical research informatics. There is an ongoing need for greater understanding of sustainability beyond what this issue provides. As more case studies of sustainability are accumulated, it is expected even more important themes will emerge from qualitative reviews that can eventually be demonstrated quantitatively.